Interpersonal relationships and drug use over time among homeless people: a qualitative study - Marília Ignácio de Espíndola; André Bedendo; Eroy Aparecida da Silva; Ana Regina Noto (BMC, 2020)
Abstract Background Homelessness is one of the most severe forms of social exclusion and is an important public health issue. It is characterized by processes of weakening of interpersonal bonds. The objective of this study was, therefore, to elucidate how interpersonal relationships change over the life cycle of homeless drug and alcohol users. Method We used a qualitative methodology. The participants were adults who had a history of homelessness and use of alcohol and other drugs. The interviews were semi structured and used a timeline instrument. All interview were audio recorded, transcribed, and submitted to thematic analysis. Results Twenty individuals participated in the study. Reports on social exclusion over time stood out in respect of four main themes and their respective subthemes: Theme 1 - Childhood: instability upbringing, abuse, violence, and an absent or not very present father figure; Theme 2 - Adolescence: school dropout and failure; acceptance of gender and sexual orientation; birth of first child, living with a partner or getting married: Theme 3 - Adulthood: estrangement or conflicting relationship with family; health problems; drug trafficking and prostitution; Theme 4 - Cross-cutting factors: death of relatives and substance use. Conclusion The results suggest that interpersonal relationships are permeated by successive breakups, conflicts and other events that start in childhood and can have a cumulative effect in later stages of life, and cross the subsequent phases. Substance abuse and dependence are mentioned as cross-cutting factors that intensify social exclusion in all stages of life.